3(x-2)-4(x-1)=-7(x+2)
Răspunsuri la întrebare
Răspuns de
1
3x-6-4x+4=7x+14
-x-2=7x+14
-8x=16
x=-16/8
x=-2
-x-2=7x+14
-8x=16
x=-16/8
x=-2
Neștiutorul32:
La trecere ai comis o greseala.
Răspuns de
1
3(x-2)-4(x-1)=-7(x+2)
3x-6-4x+4=-7x-14
3x-4x+7x=-14+6-4
6x=-12
x=-12/6
x=-2
3x-6-4x+4=-7x-14
3x-4x+7x=-14+6-4
6x=-12
x=-12/6
x=-2
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă